Jacques Loeb papers - Loeb, Jacques, 1859-1924.; Loeb, Jacques, 1859-1924.; Loeb, Jacques, 1859-1924.; Loeb, Jacques, 1859-1924.
Correspondence, speeches, writings, notebooks, biographical material, awards, photographs, and other papers pertaining primarily to Loeb's career as a physiologist. Includes drafts of his books Forced Movements, Tropisms, and Animal Conduct (1918); Proteins and the Theory of Colloidal Behavior (1922); and Regeneration from a Physico-chemical Viewpoint (1924). Also includes Loeb's laboratory notebooks relating principally to his research on bryophytes, gelatin, and frogs, which led to his development of the tropism theory; and scientific articles on such subjects as colloid chemistry, genetics, osmosis, and proteins. Correspondents include Svante Arrhenius, Bernhard Berenson, James Bryant Conant, Paul Henry De Kruif, Paul Ehrlich, Albert Einstein, Sigmund Freud, Julian Huxley, Ivan Petrovich Pavlov, Harlow Shapley, and members of the Loeb family.
Physiologist and educator.
Collection material in English and German.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Arrhenius, Svante, -- 1859-1927 -- Correspondence; Berenson, Bernard, -- 1865-1959 -- Correspondence; Conant, James Bryant, -- 1893-1978 -- Correspondence; De Kruif, Paul, -- 1890-1971 -- Correspondence; Ehrlich, Paul, -- 1854-1915 -- Correspondence; Einstein, Albert, -- 1879-1955 -- Correspondence; Freud, Sigmund, -- 1856-1939 -- Correspondence; Huxley, Julian, -- 1887-1975 -- Correspondence; Pavlov, Ivan Petrovich, -- 1849-1936 -- Correspondence; Shapley, Harlow, -- 1885-1972 -- Correspondence; Loeb family -- Correspondence; Biochemistry; Biology; Bryology; Bryophytes; Chemistry; Colloids; Frogs; Gelatin; Genetics; Osmosis; Proteins; Tropisms; Zoology; Educators; Physiologists